Improving the Quality of Islamic Religious Education Learning through Class Management in Elementary Schools - Farihin Farihin; Eem Ubada Al Mudzaifah; Ahmad Arifuddin (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to describe the planning for improving the quality of Islamic religious education learning through classroom management, the implementation of classroom management, and teachersâ€™ efforts in improving the quality of Islamic religious education learning. This study uses a qualitative approach with descriptive methods based on data collection techniques, including observation, interviews, and document analysis. The stages of data analysis include data reduction techniques, data presentation, data verification, and concluding. The results of this study showed that the classroom management planning carried out by the teacher is to prepare all the basic skills needed by the teacher in teaching. Furthermore, the implementation of classroom management is carried out through the management of face-to-face activities and the organization of subject matter embodied in the lesson plans. The teachersâ€™ efforts in maximizing classroom management include a disciplinary approach, a reward and punishment approach, a teaching approach, an attitude approach, and a group process approach. These aforementioned approaches lead to the strategy to build good interactions with students. The planning and implementation of classroom management that has been carried out by teachers is hoped to improve the quality of learning Islamic religious education in elementary schools.Keywords: improving the quality of learning, classroom management, Islamic religious education.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan perencanaan peningkatan mutu pembelajaran pendidikan agama Islam melalui manajemen kelas, implementasi manajemen kelas, dan upaya guru dalam meningkatkan mutu pembelajaran Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif yang berpijak pada teknik pengumpulan data yaitu observasi, wawancara, dan studi dokumentasi serta tahapan analisis data dengan menerapkan teknik reduksi data, penyajian data dan verifikasi data, serta penarikan kesimpulan. Hasil penelitian ini menunjukan bahwa perencanaan manajemen kelas yang dilakukan oleh guru adalah dengan mempersiapkan seluruh keterampilan dasar yang dibutuhkan oleh guru dalam mengajar. Selanjutnya, implementasi manajemen kelas dilaksanakan melalui pengelolaan kegiatan tatap muka dan pengorganisasian materi pelajaran yang diwujudkan dalam Rencana Pelaksanaan Pembelajaran (RPP). Adapun upaya guru dalam memaksimalkan manajemen kelas diantaranya adalah melalui pendekatan kedisiplinan, pendekatan reward and punishment, pendekatan pengajaran, pendekatan sikap, dan pendekatan proses kelompok. Pendekatan-pendekatan tersebut bermuara pada bagaimana guru mampu membangun interaksi yang baik dengan siswa. Sehingga diharapkan perencanaan dan implementasi manajemen kelas yang telah dilakukan oleh guru mampu meningkatkan kualitas pembelajaran pendidikan agama Islam di sekolah dasar.Kata kunci: peningkatan mutu pembelajaran, manajemen kelas, pendidikan agama Islam.